2008
DOI: 10.1007/s10853-008-2714-y
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of microstructure and microhardness in copper subjected to ultra-high strains

Abstract: The microstructure and microhardness of copper subjected to large strains either using one or a combination of severe plastic deformation (SPD) processing techniques was evaluated. The individual SPD techniques used include equal-channel angular pressing (ECAP), high-pressure torsion (HPT), and chip formation during machining (M). Microstructural characterization using orientation imaging microscopy provided detailed information on the grain sizes and misorientation statistics after different processing routes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 22 publications
5
20
0
1
Order By: Relevance
“…614) Based on the main deformation mode, the SPD processes can be divided into several groups: (i) simple shear: equal channel angular pressing 69) and continuous confined strip shearing; 10) (ii) torsion shear: high-pressure torsion, 11,12) twist extrusion, 13) high-pressure tube twisting, 14) and conecone method; 15) and (iii) compression: accumulative rollbonding 16) and multi-directional forging. 17) Along with other torsion-based SPD processes, twist extrusion (TE) recently received some interest, which is illustrated by the emergence of new techniques based on the idea of TE.…”
Section: Introductionmentioning
confidence: 99%
“…614) Based on the main deformation mode, the SPD processes can be divided into several groups: (i) simple shear: equal channel angular pressing 69) and continuous confined strip shearing; 10) (ii) torsion shear: high-pressure torsion, 11,12) twist extrusion, 13) high-pressure tube twisting, 14) and conecone method; 15) and (iii) compression: accumulative rollbonding 16) and multi-directional forging. 17) Along with other torsion-based SPD processes, twist extrusion (TE) recently received some interest, which is illustrated by the emergence of new techniques based on the idea of TE.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] The application includes the consolidation of metallic powders, [3][4][5] composites, [6][7][8][9][10][11][12] ball-milled powders, 13,14) amorphous powders, 15) amorphous ribbons, 16) and very recently machining chips. 17,18) Strain-induced amorphization was reported for some compounds, 19,20) whereas crystallization is detected in amorphous materials such as Cu 50 [21][22][23][24][25][26][27][28][29][30][31] It is well established that bulk amorphous materials have high strengths and high hardness [32][33][34][35] and it is known that processing through HPT leads to an increase in the strength of metallic materials. 1,<...>…”
Section: Introductionmentioning
confidence: 99%
“…Zhilyaev et al 17,18) found that consolidation of machining chips of copper through the application of HPT results in exceptionally high microhardness and fine microstructure. Yavari et al 15) and Sort et al 16) used the HPT for consolidation of Al-based amorphous powders and Fe-based amorphous ribbons and found an enhancement in microhardness but reported the formation of dispersed nanocrystallites in the glassy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…9], as well as composites [10,11,12,13,14], amorphous compounds [15, 16, 17, 18. 19], machining chips [20,21,22] and even ceramic powders [23].…”
Section: Introductionmentioning
confidence: 99%